From clapham junction to macondo, deepwater horizon: Risk and safety management in high-tech-high-hazard sectors: A review of English and Dutch literature: 1988–2010. (January 2020) - Swuste, Paul; van Gulijk, Coen; Groeneweg, Jop; Zwaard, Walter; Lemkowitz, Saul; Guldenmund, Frank
Highlights: 1980s and 1990s are a very productive years regarding safety theories, models and metaphors. All theories, models and metaphors emphasize organisational aspects of major accidents. The context is dynamic, a retreating government and a strong market and technology influence. Safety science does not yet have a unifying theory or model, reflecting its young age as a science. Many companies suffer from sloppy management, with a limited insight into possible disaster scenario's. Abstract: Objective: What is the influence of general management trends and safety research on managing safety? Method: A literature study which is limited to original English and Dutch books, documents, and articles in relevant scientific journals, for the period 1988–2010. Results and conclusions: Safety science does not yet have a unifying theory, which betrays its young age as a scientific discipline. In the period concerned, well-known theories, models and metaphors are established or re-issued, including the High Reliability Theory, the Man-Made Disasters and the corresponding Disaster Incubation Theory, and the Normal Accident Theory. The Swiss cheese metaphor takes its final form, the bowtie metaphor and the Drift into Danger model are published. All these theories, models and metaphors emphasize organisational aspects of major accidents in high-tech-high-hazard sectors. General management trends highlight the importance of external stakeholders, which are only reflected in the Drift into Danger metaphor. These developments must be considered in the context of a dynamic influence of external factors, like a decrease in government influence coinciding with strong market and technology developments, which can conflict with safety requirements for high-tech-high-hazard companies. Organisational/safety culture and risk/safety management systems take off during this period, both in terms of academic research and consultancy activities for companies. Whether these concepts will have a lasting influence on safety levels in companies is yet to be seen, given the unclear relationship with major accident processes. Research findings show that many companies suffer from sloppy management, having only a limited insight into possible disaster scenarios.